2019
DOI: 10.7759/cureus.5721
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Body Mass Index and Vitamin D Supplement Use among Adults in the United States

Abstract: BackgroundObesity has been consistently associated with lower 25-hydroxyvitamin D (25(OH)D) concentrations. BMI status also has a major impact on 25(OH)D levels among vitamin D supplement users. In our cross-sectional study, we aimed to discuss the prevalence of vitamin D supplement use and its effect on 25(OH)D levels according to BMI status among US adults.MethodsThe present analysis was based on data from the National Health and Nutrition Examination Survey (NHANES) cycles 2011-2012 through 2013-2014. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
(32 reference statements)
3
12
0
Order By: Relevance
“…The results of the current study on vitamin D and calcium intake are in agreement with those found in another study in Americans aged ≥19 years, which reported also insufficient vitamin D intake and supplement intake and sufficient calcium intake/supplement intake across all BMI categories (55). Another study also showed that obese adults have a lower intake of dietary supplements compared to overweight, and normal weight adults (56)(57)(58). In the current study, older adults with obesity also had the highest deficiencies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the current study on vitamin D and calcium intake are in agreement with those found in another study in Americans aged ≥19 years, which reported also insufficient vitamin D intake and supplement intake and sufficient calcium intake/supplement intake across all BMI categories (55). Another study also showed that obese adults have a lower intake of dietary supplements compared to overweight, and normal weight adults (56)(57)(58). In the current study, older adults with obesity also had the highest deficiencies.…”
Section: Discussionsupporting
confidence: 91%
“…The pooled mean for vitamin D intake was 6 ug [95% CI [4][5][6][7][8][9]. For 25(OH)D, the pooled mean was 54 nmol/L [95% CI [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62], 52 nmol/L [95% CI [46][47][48][49][50][51][52][53][54][55][56][57][58], and 48 nmol/l [95% CI in normal (N = 7), combined overweight and obese (N = 12), and obese older adults (N = 4), respectively. In conclusion, older adults with overweight and obesity have a borderline sufficient protein and sufficient calcium intake, but insufficient vitamin D intake.…”
mentioning
confidence: 99%
“…According to the Australian Bureau of Statistics, in 2017–2018, 67.0% of Australian adults were overweight and obese, an increase from 63.4% in 2014–2015 64. Current literature shows a consistent association between obesity and low vitamin D concentrations as well as lower vitamin D supplementation intake 65 66. Possible mechanisms for lower serum vitamin D status in obese individuals have been proposed,67 68 and given the growing literature on the association between obesity and low vitamin D concentrations, it would be interesting to include the body mass index of patients to elucidate this possible association.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for these contradictory results were attributed to unmeasured predictors of vitamin D status such as vitamin D intake and sun exposure [ 15 ]. Lower 25(OH)D concentrations have been consistently reported across different latitudes in obese subjects compared with their normal-weight counterparts, which have been related to limited sun exposure, decreased bioavailability of vitamin D in fat tissue, and lower vitamin D supplements use [ 22 - 25 ]. As expected, the present results also demonstrated an inverse relationship between BMI and 25(OH)D concentrations among older adults.…”
Section: Discussionmentioning
confidence: 99%